Assessing the Spatial Sustainability of Urban Bus Transit: A Socioeconomic Sustainability Perspective - Fei Shi; Jingang Zhang; Tiantian Wu (Journal of Advanced Transportation, 2025)
To promote the sustainable development of urban bus transit, this paper introduces the concept of spatial sustainability for bus networks. This concept aims to achieve a balance in the spatial distribution of bus routes, optimizing both social and economic benefits. The paper presented a novel approach that utilizes multisource big data to assess the spatial sustainability of bus transit, with a specific focus on the existing transit-supportive area (TSA) method. In this study, we employed various data sources, including mobile phone signaling data, residential travel survey data, map API data, and bus credit card data. These datasets were used to identify regions where peak-hour ridership exceeded a defined threshold. Using Nanjing as a case study, we defined the bus sustainable development zone (BSDZ) by evaluating areas where peak-hour bus ridership exceeded 10 trips per grid. The study then compared the BSDZ with both the bus support zone and the bus stop service zone. In addition, we conducted a comparative analysis between the BSDZ and TSA, as well as the existing bus service areas. The findings revealed a spatial imbalance in the current bus network and highlighted areas where optimization was needed. The identified BSDZs offered valuable insights that can serve as a reference for future bus route optimization in Nanjing, contributing to a more balanced and efficient transit system.